A Case Study of a High School Mathematics Professional Learning Community in Ontario - Kelly, McKie (Université d'Ottawa / University of Ottawa, 2016)
This qualitative study offers an in-depth description of a high school professional learning community (PLC) as it focuses on enhancing the teaching and learning of the Grade 9 Applied Mathematics curriculum. The teachers’ goal in this PLC is to implement strategies they believe best meet the needs of their students. Over the course of one school year data was collected during PLC meetings and through individual participant interviews. Data was analyzed and used to answer the following research questions: How is a PLC formed and sustained, and how does it evolve throughout the process of teachers examining their practice? What happens when a professional community of learners comes together to discuss, dissect and reflect on their own practice with the intention of broadening their understanding of teaching mathematics? Analysis of the data revealed that teachers came together through their shared work of teaching in ways that address the needs of students in applied level mathematics. Through external funding and strong leadership and support from the school Principal, this PLC created opportunities to meet and collaborate. During meetings the PLC members discussed their pedagogical challenges, focused on the needs of students and student learning, designed lessons that would specifically target the needs of their students, observed each other teach these co-designed lessons, and finally discussed and reflected on the taught lesson. This process was repeated throughout the year, each time building on lessons learned from previous experiences. Although the PLC members described how being out of their class to collaborate did pose some challenges, overall they described their experience in the PLC as the most powerful professional development of their careers.
Keywords: mathematics; education; PLC; professional learning